The impact of herbal medicine in regulating intestinal flora on female reproductive disorders - Liu, Min; Yan, Jin; Wu, Yeke; Zhu, Hongqiu; Huang, Yefang; Wu, Keming (Frontiers in Pharmacology, 2022)
As an important part of the human intestinal microecology, the intestinal flora is involved in a number of physiological functions of the host. Several studies have shown that imbalance of intestinal flora and its regulation of the intestinal barrier, intestinal immune response, and intestinal flora metabolites (short-chain fatty acids and bile acids) can affect the development and regression of female reproductive disorders. Herbal medicine has unique advantages in the treatment of female reproductive disorders such as polycystic ovary syndrome, endometriosis and premature ovarian insufficiency, although its mechanism of action is still unclear. Therefore, based on the role of intestinal flora in the occurrence and development of female reproduction-related diseases, the progress of research on the diversity, structure and composition of intestinal flora and its metabolites regulated by botanical drugs, Chinese herbal formulas and active ingredients of Chinese herbal medicines is reviewed, with a view to providing reference for the research on the mechanism of action of Chinese herbal medicines in the treatment of female reproductive disorders and further development of new herbal medicines.